Ramalan Timur Kuran Tentang Masa Depan Ekonomi Islam: Sebuah Respons - Ahmad Ubaidillah (Universitas Islam Lamongan, 2016)
Many fundamentalist religious movements have economic agenda. The movements emerge to reconstruct the economic system in accordance with the provisions of their respective religions. Therefore, we often hear Christian economics, Buddhist Socialism, Hindu economics, or Islamic economics. The main agenda of economic fundamentalist movements look different from conventional economics (Capitalism and Socialism). Every economic agenda that they propose has different philosophical characteristics and heritage and unique discourse. In this paper, author tries to elaborate Timur Kuran’s ideas, a pioneer of the school of critical alternatives in the tradition of Islamic economic thought, on future of Islamic economics Islam which is considered a manifestation of the economic doctrine of the fundamentalist Islamic group. Why is the future of Islamic economics addressed pessimistic by Kuran and what offer is given by Kuran to give response to Islamism’s Islamic economics are some questions that will be answered in the following discussion. In this study, the writer also will respond Kuran’s predictions about the future of the Islamic economics. The analytical method used in this study is taxonomic analysis, which is not only a general analysis, but also a specific domain that is very useful to describe the phenomenon or problem that is to be the target of the research. In this analysis, the domains are selected to be studied in depth is the focus of study that needs to be tracked each other's internal structures in more detail and depth. Overall, this technique uses